Low-Temperature Direct Growth of Amorphous Boron Nitride Films for High-Performance Nanoelectronic Device Applications - Sattari-Esfahlan, Seyed Mehdi; Kim, Hyoung Gyun; Hyun, Sang Hwa; Choi, Jun Hui; Hwang, Hyun Sik; Kim, Eui Tae; Park, Hyeong Gi; Lee, Jae Hyun (ACS Applied Materials and Interfaces, 2023)
We successfully demonstrated the improvement and stabilization of the electrical properties of a graphene field effect transistor by fabricating a sandwiched amorphous boron nitride (a-BN)/graphene (Gr)/a-BN using a directly grown a-BN film. The a-BN film was grown via low-pressure chemical vapor deposition (LPCVD) at a low growth temperature of 250 °C and applied as a protection layer in the sandwiched structure. Both structural and chemical states of the as-grown a-BN were verified by various spectroscopic and microscopic analyses. We analyzed the Raman spectra of Gr/SiO2 and a-BN/Gr/a-BN structures to determine the stability of the device under exposure to ambient air. Following exposure, the intensity of the 2D/G-peak ratio of Gr/SiO2 decreased and the position of the G and 2D peaks red-shifted due to the degradation of graphene. In contrast, the peak position of encapsulated graphene is almost unchanged. We also confirmed that the mobility of a-BN/Gr/a-BN structure is 17,941 cm2/Vs. This synthetic strategy could provide a facile way to synthesize uniform a-BN film for encapsulating various van der Waals materials, which is beneficial for future applications in nanoelectronics.
Keywords: Amorphous boron nitride; Boron nitride encapsulation; Boron nitride films; Direct growth; Field effect transistor; Field-effect transistor; High mobility; Lows-temperatures; Nitride structures; amorphous boron nitride (a-BN); boron nitride encapsulation; field effect transistor (FET); graphene; heterojunction; high mobility